The role of process information in narrations while learning with animations and static pictures. (January 2017) - Stebner, Ferdinand; Kühl, Tim; Höffler, Tim N.; Wirth, Joachim; Ayres, Paul
Abstract: The role of process information in annotating narrations used for learning with animations compared to static pictures is examined. In two experiments, seventh and eighth graders from German high schools were randomly assigned to learning environments which differed in the combination of visualization (no visualization vs. static pictures vs. animation) and type of narration (no narration vs. non-process narration vs. process narration). Results revealed that visualizations were necessary for this kind of instructional material to gain a deeper understanding. Moreover, the results consistently show a significant superiority of animations over static pictures. Concerning narrations, results display a significant superiority of process descriptions only in Experiment 1. Contrary to prior assumptions, the interaction of specific information in narrations with the type of visualizations was not significant. Highlights: Animations are superior to static pictures when learning chemical processes. The presence of visualizations and the presence of narrations facilitated learning. Type of narrations does not moderate learning with animations and static pictures.